Pechan Coffee Enterprise / Nuradriana Athirah Shamsul Bahari... [et al.] - Shamsul Bahari, Nuradriana Athirah; Mazla @ Mazlan, Nur Wajihah; Rosdi, Nur Hamidah Dayyini; Abd Aziz, Nur Umairah; Muhammad Sani, Nur Miza Syafiqa (2021)
Pechan Coffee will produce and provide coffee that is the first beverage people consume in the morning. Our primary strategy is to produce a type of drink that most customers cannot afford to experience in other places, which will satisfy their appetite. We also want to make a drink that encompasses all their needs and can be shared with their family and friends. Since our company is listed as a new company in the market, it is clear that there are many aspects that we need to consider so that our company is able to compete in the market and meet customer needs, as there are many people involved in business nowadays. In conclusion, we hope that Pechan Coffee will be a well-known food business throughout the country and be able to provide greater services from time to time. We also believe the demand for our coffee will increase every year with the increase in the human population. Last but not least, it is our pleasure to be the benchmark for other people who are interested in starting a drink business